Anticancer effects of OSW-1 on glioma cells via regulation of the PI3K/AKT signal pathway: A network pharmacology approach and experimental validation in vitro and in vivo - Zhan, Zhixin; Liu, Ziqiang; Zhang, Chaochao; Gao, Haijun; Lai, Jiacheng; Chen, Yong; Huang, Haiyan (Frontiers in Pharmacology, 2022)
Background: Gliomas are the most common primary intracranial malignant tumors with poor prognosis, despite the remarkable advances in medical technology that have been made. OSW-1, isolated from Ornithogalum saundersiae, possesses anticancer activity against various malignant cancer cells. However, the effects of OSW-1 on gliomas and its potential mechanisms remain unclear. Methods: Network pharmacology was employed for predicting potential key targets and mechanisms of the anticancer effects of OSW-1 on glioma. Experiments, including the Cell Counting Kit-8, colony formation, and flow cytometry, were performed to investigate how OSW-1 affects the biological behavior of glioma cells in vitro. Western blotting was used to detect changes in related proteins, such as those involved in the cell cycle, apoptosis, and signaling pathways. The nude mouse xenograft model was used to detect the effect of OSW-1 on inhibiting the proliferation of glioma cells in vivo. Results: An “OSW-1-Targets-Glioma” intersection network consisting of 151 intersecting genes was acquired to construct a “Protein–Protein Interaction network” and predict the top 10 core targets. According to the Kyoto Encyclopedia of Genes and Genomes pathway analysis, the PI3K/AKT signaling pathway was the top 3-ranked pathway, with 38 enriched intersecting genes. The glioma T98G and LN18 cell lines was were used to verify the predictions. OSW-1 significantly inhibited the viability and proliferation of glioma cells in a dose- and time-dependent manner. Flow cytometry showed that OSW-1 arrested the cell cycle at the G2/M phase, and the apoptotic ratio of glioma cells increased significantly with increasing concentrations. Western blotting revealed that the expression levels of p-PI3K and p-AKT1 in glioma cells treated with OSW-1 were significantly lower than those in the controls; however, 740Y-P, a PI3K activator, significantly reversed the inactivation of the PI3K/AKT signaling pathway caused by OSW-1. Furthermore, the mouse xenograft model confirmed the suppressive effect of OSW-1 on tumor growth in vivo. Conclusion: OSW-1 is a promising anti-glioma chemotherapeutic drug owing to its anticancer effects via downregulation of the PI3K/AKT signaling pathway. However, OSW-1 still has a long way to go to become a real anti-glioma drug.